Aktualitas Asas Itikad Baik dalam Praktik Pagang Gadai Sawah di Sumatera Barat - Almira, Lara Delanosa; Syechkant, Ibnu; Ikhsan, Muhammad; Syamsudin, M. (Wajah Hukum, 2025)
This study discusses the actuality of the principle of good faith in the practice of pawning rice fields in West Sumatra, especially in the context of Minangkabau customary law and Government Regulation in Lieu of Law Number 56 of 1960. This study aims to understand the application of the principle of good faith and identify the factors that become obstacles in the practice of pawning land. This type of research is a sociological legal research type. The object of the study is the rice fields, which are the objects of pawning. The subjects of the study are the Head of the Minangkabau Natural Customary Council (LKAAM) of West Sumatra and the Head of the Nagari Customary Council. The empirical legal research approach has a descriptive analytical nature with data collection techniques through observation, interviews, literature studies and documents. The analysis method is carried out descriptively and qualitatively. The results of this study indicate that the practice of pawning in Minangkabau has a matrilineal customary system and a high pusako property concept. The principle of good faith is very important in this practice, with both parties having to act honestly and fairly. However, there are several constraining factors such as legal developments, time periods, pawn requirements, and communication. Therefore, it is important to maintain the continuity of pawn practices and improve existing regulations by implementing the principle of good faith.